Curcumin oil and Grapeseed oil can antagonize the Effect of All-Trans-Retinoic Acid (ATRA) on Rat's Kidney - Khabat A. ALI (Zanco Journal of Pure and Applied Sciences, 2020)
Tretinoin chemically is all-trans retinoic acid associated with retinol groups. It is yellow to light orange crystalline powder that urges the cytodifferentiation and diminish proliferation of acute promyelocytic leukemia (APL) cells in culture and in vivo. The accurate mechanism operation of tretinoin is uncharted. Researchers have shown that tretinoin has potentially teratogenic and toxic side influences in mice, rats, hamster rabbits and patients. The most frequent adverse events in kidney were renal insufficiency, dysuria, acute renal failure, micturition recurrence and renal tubular necrosis and also it causes enlargement of prostate. There were no adequate and well-controlled studies in animal models. So, monitoring of kidney functions with its texture had to be done. In recent years herbal extract treatment showed capability of ameliorative role for the disturbance of organs functions with toxic and injuries in different tissues especially kidney tissue. Current research was conducted in 28 days and 49 rats were included and they were divided into seven groups each group containing 7 rats: the first was negative control group gavageed with olive oil at dose (2ml/kg/bw) , while the second and third were positive control groups administrated at dose (15&30 mg/kg/bw) respectively with ATRA ,indeed the others treated groups combinations between the two ATRA concentrations with curcumin oil at dose (50 mg /kg/bw) were included the fourth and fifth groups respectively, and the last two groups administrated grape oil at dose (50 mg /kg/bw) were included the sixth and seventh group respectively. From this study, we discovered that treating the rats by extracted grapeseed oil with ATRA recovered the damaged kidney architecture near to normal as well as improved their renal functions.